The Biodiversity of Tunicate (Ascidiacea) in the waters of Badi Island, Pangkajene Regency of South Sulawesi - Magdalena Litaay (International Journal of Applied Biology, 2022)
Tunicates belongs to Urochordate that inhibit coral reefs ecosystem. The uniqueness of the tunic can be seen from the body shape like a tube with 2 siphons and the body is covered by a protective layer known as the tunic. The present study aims to observe marine tunicate at waters of Badi Island, Pangkajene Regency, South Sulawesi. This research using the Belt Transect method with a length of 20 m and a width of 4 m at a depth of 5 m with 4 station points according to the wind directions. All tunicate inside transect was noted and identified. Identification was based on morphological characteristics. The result shows that there were 18 species of tunicates present in the coral reefs ecosystem of Badi Island.